Solubilities, Densities and Refractive Indices of Rubidium Chloride or Cesium Chloride in Ethanol Aqueous Solutions at Different Temperatures - 赵文霞 胡满成 蒋育澄 李淑妮 (Chinese journal of chemistry, 2007)
The data of solubilities, densities and refractive indices of rubidium chloride or cesium chloride in the system CEHsOH-H2O were measured by using a simple accurate analytical method at different temperatures, with mass fractions of ethanol in the range of 0 to 1.0. In all cases, the presence of ethanol significantly reduced the solubility of rubidium chloride and cesium chloride in aqueous solution. The solubilities of the saturated solutions were fitted via polynomial equations as a function of the mass fraction of ethanol. The CsC1-C2H5OH-H2O ternary system appeared in two liquid phases： alcoholic phase and water phase, when the mass fractions of ethanol were in the range of 10.37% to 49.59% at 35 ℃. Density and refractive index were also determined for the same ternary systems with varied unsaturated salt concentrations. Values for both experiment and theory were correlated with the salt concentrations and proportions of alcohol in the solutions. The equations proposed could also account for the saturated solutions.